Darby and Joan. Series 1 [videorecording (DVD)] - Rowe, Glenys; Gwynne, Phillip, 1958- (Acorn, 2022)
Two lone strangers trekking on the road -- a retired Australian policeman with a dog as his only company and a widowed English nurse -- meet each other and embark on an epic odyssey in the outback of northern Australia. Joan is looking for answers about her husband's unusual death and Jack is just wandering to escape his past, but together they encounter mysteries in the dark corners of the isolated landscape.